Textual amulets from antiquity to early modern times: the shape of words - Theis, Christoffer; Vitellozzi, Paolo (Bloomsbury Academic, 2022)
"Comparing amulets over time and space, this volume focuses on the function of written words on these fascinating artefacts. Ranging from Roman Egypt to the Middle Ages and the Modern period, this book provides an overview on these types of artefacts in the Mediterranean world and beyond, including Europe, Iran and Turkey. A deep analysis of the textuality of amulets provides comparative information on themes and structures of the religious traditions examined. A strong emphasis is placed on the material features of the amulets and their connections to their ritual purposes. The textual content, as well as other characteristics, is examined systematically, in order to establish patterns of influence and diffusion. The question of the production, which includes the relationship that linked professional magicians, artists and craftsmen to their clientele, is also discussed, as well as the sacred and cultural economies involved."--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte 500 v. Chr.-2000; Schrift; Amulett